2006
DOI: 10.1093/eurheartj/ehi719
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age and gender on in-hospital and late mortality after acute myocardial infarction: increased early risk in younger women

Abstract: The higher 1-year mortality following AMI in women is explained by the higher risk of death in young women during the first days of hospitalization. Further investigations are crucial to determine the cause in order to improve the chance of survival in younger women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
45
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 27 publications
9
45
1
4
Order By: Relevance
“…18 Both of these reports included overall AMI patients and did not examine STEMI patients in particular. 14,18 In our analysis, women who sustained very early deaths in our STEMI subpopulation were older, had slightly different risk profiles, and underwent revascularization and reperfusion less frequently than men. Whether the excess very early death among *ORs, which are for women vs men, were adjusted for age, race, BMI, insurance type, systolic blood pressure, cardiac diagnosis, initial ECG with diagnostic ST-segment elevation or left bundle-branch block, diabetes, hypertension, hyperlipidemia, heart failure, previous MI, peripheral vascular disease, renal insufficiency, stroke, chronic obstructive pulmonary disease, and adult history of smoking.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…18 Both of these reports included overall AMI patients and did not examine STEMI patients in particular. 14,18 In our analysis, women who sustained very early deaths in our STEMI subpopulation were older, had slightly different risk profiles, and underwent revascularization and reperfusion less frequently than men. Whether the excess very early death among *ORs, which are for women vs men, were adjusted for age, race, BMI, insurance type, systolic blood pressure, cardiac diagnosis, initial ECG with diagnostic ST-segment elevation or left bundle-branch block, diabetes, hypertension, hyperlipidemia, heart failure, previous MI, peripheral vascular disease, renal insufficiency, stroke, chronic obstructive pulmonary disease, and adult history of smoking.…”
Section: Discussionmentioning
confidence: 89%
“…In 1 report paralleling our findings, the largest sex disparity in death rates after AMI occurred in the early hospitalization period, namely, during the initial 5 days of hospitalization. 14 Another study demonstrated increased case fatality after AMI in the initial 24 hours of hospitalization but did not find sex differences in case fatality during this time period. 18 Both of these reports included overall AMI patients and did not examine STEMI patients in particular.…”
Section: Discussionmentioning
confidence: 94%
“…Age was significantly associated with excess mortality even after adjusting for sex, comorbidities, and treatments. However, care must be taken in interpreting this result because it is possible that other unmeasured comorbidities were present in the older adults that may have biased the estimates 36, 37…”
Section: Discussionmentioning
confidence: 99%
“…In ongoing studies in recent decades gender-related issues in prognosis and treatment strategies were analyzed, but with no comment on CS [22][23][24][25]. Many studies have shown that poor clinical outcomes in women are related to suboptimal [26][27][28][29]. Conversely, several lines of evidence indicate that guidelines-compliant treatment in women and men results in significant improvements in outcomes [30].…”
Section: Bmi -Body Mass Index (Kg/m 2 ) MI -Myocardial Infarction Pmentioning
confidence: 99%